Computerized cognitive performance assessments in the Brooklyn Cognitive Impairments in Health Disparities Pilot Study. Issue 11 (1st November 2019) - Adler, Kerry; Apple, Samuel; Friedlander, Alison; Cheng, Frank; Cohen, Carl; Levine, Steven R.; Lucchesi, Michael; Maruff, Paul; Reinhardt, Michael; Salmieri, Margaret; Stevens, David; Weingast, Sarah; et al.
Abstract: Introduction: Detecting cognitive impairment in diverse, health disparities communities is an urgent health care priority. Methods: The Brooklyn Cognitive Impairments in Health Disparities Pilot Study investigated quantitative aspects and liking of a computerized cognitive performance assessment, Cognigram, among individuals ≥ 40 years in traditional and nontraditional primary care settings. Results: Cognigram was piloted in the Emergency Department, Family Medicine, and Geriatric Psychiatry clinics: 58 adults (23 men, 35 women), 67.9 ± 9.8 years (range 43–91), completed the Cognigram and 5‐item liking survey. The observed liking range was 2 to maximum score 5 (67% scored 4–5; no sex or age differences). Discussion: The Cognigram was well liked in waiting rooms of primary care settings. Assistance from a trained adult and clinic endorsement were keys to success. How the Cognigram performs in a geographically compact, population‐dense global setting, such as Brooklyn with high vascular disease risk and a plethora of health disparities, is being tested. Highlights: Cognigram is the first‐ever computerized cognitive assessment in central Brooklyn. Cognigram is well liked in health disparity primary care settings. Challenges regarding implementation across several clinics were met. Diversity was embraced, and successful administration was achieved.